A clash of heroes : Brandeis, Weizmann, and American Zionism - Halpern, Ben. (New York : Oxford University Press, 1987)
This book examines the conflict between Louis D. Brandeis and Chaim Weizmann, two heroes of a crucial era in recent Jewish history. The author considers how each man confronted the problem of his Jewish identity and the extent to which they both served as models for rival solutions.
INTRODUCTION: HEROES AND THEIR PUBLIC; 1 WEIZMANN; 2 BRANDEIS; 3 WARTIME LEADERSHIP; 4 ENCOUNTER AND CLASH; 5 EPILOGUE AND CONCLUSIONS; NOTES; INDEX.
Includes bibliographical references (pages 271-286) and index.
English.
eBooks on EBSCOhost
Keywords: Brandeis, Louis D., -- 1856-1941.; Weizmann, Chaim, -- 1874-1952.; Zionist Commission; Brandeis, Louis D., -- 1856-1941; Weizmann, Chaim, -- 1874-1952; Zionist Commission; Zionism -- United States; Zionists -- Biography; HISTORY; Zionism; Zionists; United States; Biographies; Biographies; Biographies